Does obesity Kuznets curve exist in developing economies? Evidence from 38 African countries based on heterogeneous panel data analysis on income-level classification - Chen, Hao; Atingabili, Samuel; Mensah, Isaac Adjei; Yaw Omari-Sasu, Akoto; Agba Tackie, Evelyn; Arboh, Francisca; Danso, Bertha Ada (Frontiers in Public Health, 2023)
Introduction The global pandemic disease known as the obesity epidemic has spread throughout the planet. Particularly, Africa is facing a growing problem of obesity, and the trend is rising. This is a result of a ticking time bomb. Given the claim that multiple socio-economic factors significantly affect the diversity in obesity rates between nations, economic development can be seen as a key contributor to this variation. Methods Relying on the aforementioned avowal, this extant research examines the relationship between obesity and economic growth using urbanization, trade openness, and unemployment as intermittent variables within the Obesity Kuznets Curve (OKC) framework. Using panel data from 1990 to 2020, a panel of 38 African countries subdivided into income levels (Low income, Lower-middle income, and Upper-middle income) were analyzed. With the presence of residual cross-sectional reliance and slope heterogeneity, the Augmented Mean Group (AMG) econometric approach is employed. Results Key outcomes from the mentioned estimation method unveiled that economic growth positively impacts obesity among all the study panels. Variably, unemployment was evidenced to have a palpable positive impact on obesity concerning Low-income economies whereas on the side of the Lower-middle income panel together with Upper-middle income economies and the aggregated panel, a significant negative relationship is observed with obesity. Further, urbanization enhanced obesity in the Low-income panel and the aggregated panel of African nations, whereas an adverse effect is identified in both the Lower-middle and Upper-middle economies in Africa. Moreover, except for Low-income African economies, all the other panels of African nations in terms of income levels were noted to have a significant negative effect on obesity from trade openness. Discussion Finally, the long-run coefficients indicated that the OKC is valid among all panels of African countries. The study thus preferably suggests in African economies that addressing the inverted U-shape relationship between obesity and economic growth requires a multifaceted approach that considers the evolving dynamics of both factors. Policy makers should, therefore, aim to balance promoting economic growth and safeguarding public health through targeted interventions and long-term strategies.